Metagenomic insights into traditional fermentation of rice-based beverages among ethnic tribes in southern Assam, Northeast India - Yumnam, Hanna; Hazarika, Parijat; Sharma, Indu (Frontiers in Microbiology, 2024)
Traditional fermented foods have long been recognized for their numerous health benefits along with their potential to aid in the treatment of gastrointestinal disorders. These fermented foods have been shown to promote gut health and contribute to a longer, healthier life. In this study, high-throughput sequencing using the Illumina MiSeq platform was employed to investigate the microbiome communities of rice-based fermented beverages consumed by ethnic tribes in Southern Assam, namely Zeme Naga, Dimasa Kachari, Hmar, Karbi and Tea tribe. The fermented rice-based beverages were highly predominated by Firmicutes, Bacteroides, Proteobacteria, and Actinobacteria exhibiting the highest relative abundance across all tribes. At genus level, significant abundance of Pediococcus, Lactobacillus, Bacillus, Leuconostoc, Acetobacter, Staphylococcus, Delftia, Erwinia, Klebsiella and Chrysebacterium were found amongst these ethnic tribes. Understanding the fermented food microbiome will help to know the relationships between microbial communities and their effect on health of humans amongst the tribes.Furthermore, the use of these fermented products could provide enhanced health benefits to Southern Assam region of India.